Expression of complement and toll-like receptor pathway genes is associated with malaria severity in Mali: a pilot case control study. (December 2016) - Sobota, Rafal; Dara, Antoine; Manning, Jessica; Niangaly, Amadou; Bailey, Jason; Kone, Abdoulaye; Thera, Mahamadou; Djimdé, Abdoulaye; Vernet, Guy; Leissner, Philippe; Williams, Scott; Plowe, Christopher; et al.
Abstract Background The host response to infection byPlasmodium falciparum, the parasite most often responsible for severe malaria, ranges from asymptomatic parasitaemia to death. The clinical trajectory of malaria is influenced by host genetics and parasite load, but the factors determining why some infections produce uncomplicated malaria and some proceed to severe disease remain incompletely understood. Methods To identify molecular markers of severe falciparum malaria, human gene expression patterns were compared between children aged 6 months to 5 years with severe and uncomplicated malaria who were enrolled in a case–control study in Bandiagara, Mali. Microarrays were used to obtain expression data on severe cases and uncomplicated controls at the time of acute disease presentation (five uncomplicated and five severe), 1 week after presentation (three uncomplicated and three severe) and treatment initiation, and in the subsequent dry season (late convalescence, four uncomplicated and four severe). This is a pilot study for the first use of microarray technology in Mali. Results Complement and toll-like receptor (TLR) pathways were differentially expressed, with severe cases showing higher expression of theC1q, TLR2, TLR4, TLR8, andCR1 genes. Other genes previously associated with malaria pathogenesis, GZMB, FOS andHSPA6, were also higher among severe cases.TLR2, TLR4, TLR8, CR1, GZMB, FOS, andHSPA6 genes were expressed at lower levels in severe cases at late convalescence. Conclusions Overexpression of genes previously associated with uncomplicated malaria was associated with severe disease. Low baseline expression of these genes may represent candidate markers for severe malaria. Despite the small sample size, results of this pilot study offer promising targets for follow-up analyses.